PENGARUH WORK LIFE BALANCE DAN JOB EMBEDDEDNESS TERHADAP TURNOVER INTENTION DENGAN ORGANIZATIONAL COMMITMENT SEBAGAI VARIABEL MEDIASI - Muhammad Faisal Ramadanu (2022)
This study aims to analyze work life balance and job embeddedness on turnover intention with organizational commitment as a mediating variable (Case Study on Millennial Employees of PT. United Chemicals Inter Aneka). The sample of respondents in this study were 80 millennial employees who were used through an electronic questionnaire. Using quantitative methods with data analysis techniques using Structure Equation Models (SEM) using Partial Least Square (PLS). This study shows that work life balance has an effect on turnover intention, while job embeddedness is found to have no effect on turnover intention. Although work life balance and job embeddedness have a significant effect on organizational commitment, work life balance and job embeddedness through organizational commitment as a mediating variable have no effect on turnover intention.